Magnetics and spintronics on two-dimensional composite materials of graphene/hexagonal boron nitride. (December 2017) - Wang, Jingang; Xu, Xuefeng; Mu, Xijiao; Ma, Fengcai; Sun, Mengtao
Abstract: Since its discovery, graphene has become a magnetic electronic device with its unique magnetic properties (weak spin-orbit coupling, longer spin coherence, giant magnetoresistance, and longer spin relaxation time), which make it become the ideal preparation material for spin electronic devices. On the other hand, two-dimensional hexagonal boron nitride (h-BN) crystals with the same lattice structure as graphene but different in electronic properties. With its unique magnetic properties (semi-metallic magnetic, spin selective, spin transport), which make it has potential applications in terms of spin electronics and other applications. Especially the graphene/h-BN heterostructure, the performance is clearly different from the excellent magnetic and spin electron properties (no attenuation of the transmission characteristics, magnetic tunneling resonance, etc.), making the graphene/h-BN heterostructure becomes ideal since spin electronic materials. Here, we review graphene, h-BN, and their heterogeneous structure, their magnetic applications and spintronics in the unique performance. Graphical abstract: Highlights: We review Magnetics and spintronics of graphene. We review Magnetics and spintronics of hexagon boron nitride (h-BN). We review Magnetics and spintronics graphene/h-BN heterostructure.